Enhancement of the sensitivity of valacyclovir and acyclovir for their spectrofluorimetric determination in human plasma1. Issue 96 (17th October 2015) - Derayea, Sayed M.; Omar, Mahmoud A.; Mostafa, Islam M.; Hammad, Mohamed A.
<x xml:space="preserve">Abstract</x> Two rapid, simple and highly sensitive spectrofluorimetric methods have been developed and validated for determination of valacyclovir hydrochloride (VAC) and acyclovir (ACV).